What Is the Role of AI in Microbiology Diagnostics? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is rapidly transforming the landscape of medical microbiology, offering powerful new tools to enhance pathogen detection, predic...
Keywords: AI in Laboratory Medicine; Microbiology; Diagnostics; Artificial Intelligence; Machine Learning; Deep Learning; Clinical Decision Support